Combined inkjet printing and infrared sintering of silver nanoparticles using a swathe-by-swathe and layer-by-layer approach for 3-dimensional structures - Vaithilingam, Jayasheelan; Simonelli, Marco; Saleh, Ehab; Senin, Nicola; Wildman, Ricky D.; Hague, Richard J. M.; Leach, Richard K.; Tuck, Christopher J. (American Chemical Society, 2017)
Despite the advancement of additive manufacturing (AM)/3-dimensional (3D) printing, single-step fabrication of multifunctional parts using AM is limited. With the view of enabling multifunctional AM (MFAM), in this study, sintering of metal nanoparticles was performed to obtain conductivity for continuous line inkjet printing of electronics. This was achieved using a bespoke three dimensional (3D) inkjet-printing machine, JETx®, capable of printing a range of materials and utilizing different post processing procedures to print multi-layered 3D structures in a single manufacturing step. Multiple layers of silver were printed from an ink containing silver nanoparticles (AgNPs) and infra-red sintered using a swathe-by-swathe (SS) and layer-by-layer sintering (LS) regime. The differences in the heat profile for the SS and LS was observed to influence the coalescence of the AgNPs. Void percentage of both SS and LS samples was higher towards the top layer than the bottom layer due to relatively less IR exposure in the top than the bottom. The results depicted a homogeneous microstructure for LS of AgNPs and showed less deformation compared to the SS. Electrical resistivity of the LS tracks (13.6 ± 1μΩ cm) was lower than the SS tracks (22.5 ± 1 μΩ cm). This study recommends the use of LS method to sinter the AgNPs to obtain a conductive track in 25% less time than SS method for MFAM.